Analysis of Temperature Changes, Vegetation, Evapotranspiration, and Drought Based on Modeling of Landsat 5 and 8 Satellite Imagery and Meteorological Indicators - Mitra Sadat Fathifard; Abbas Rahdan; Mahsa Tohidfar (اکولوژی انسانی, 2023)
Given the importance of evapotranspiration in the hydrological cycle and its diverse applications in various scientific fields, calculating its value, particularly actual evapotranspiration, is of great significance. Since vegetation cover is one of the most important factors influencing land surface temperature, the present study aims to investigate the spatial autocorrelation between land surface temperature and evapotranspiration in relation to vegetation cover in Maraveh Tappeh County. In the first part of the study, a high-resolution MODIS dataset was processed and analyzed seasonally for each year over a time period spanning 2000, 2010, 2015, and 2020 using the Google Earth Engine platform. Evapotranspiration was then calculated using MODIS data and the Torrent-White method, incorporating the vegetation growth coefficient, and compared with evapotranspiration values derived from the SEBAL algorithm. Additionally, drought prediction was conducted using the Standardized Precipitation Index (SPI) (1-month, 3-month, 6-month, and 12-month) for the period from 2015 to 2044. To identify and uncover patterns and trends in the spatial data, ArcGIS software was utilized after calculating the changes. To achieve the best results with minimal error, the Inverse Distance Weighting (IDW) method with exponential dispersion was employed, and statistical indices such as Root Mean Square Error (RMSE) and Mean Absolute Error (MAE) were used to select the best interpolation method. The results indicated that the Inverse Distance Weighting method was the most effective among the methods used for estimating changes. The findings of this study revealed that in spring, the highest percentage of NDVI does not spatially coincide with the lowest temperature; in other words, the vegetation index percentage does not exhibit an inverse relationship with land surface temperature. In summer, the highest percentage of the vegetation index spatially aligns completely with the lowest land surface temperature. In winter, the distribution pattern of temperature is entirely different compared to other seasons due to the moderating role of vegetation cover through the mechanism of evapotranspiration.